An in-depth review of the critical water analysis parameter and water quality management technology in cage aquaculture within Malaysian coastal regions - Norhafini Hambali,; Ab Aziz Mohd Yusof,; Nurul Hazwani Sabri,; Wan Nur Fazlina Abdol Jani,; Mohammad Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Cage fish farming in Malaysia’s coastal areas is a significant industry that provides food and income for local communities. Since the country’s catch-fishing resources have been fully exploited, there is a huge market for developing the aquaculture industry to increase fish output and supply. However, disease outbreaks, pollution, and environmental degradation must be addressed to ensure sustainable and environmentally responsible practices. This can result in increased stress levels and susceptibility to diseases, ultimately impacting the overall well-being of fish populations within the aquatic ecosystem. Water quality plays a crucial role in fish farming as it significantly impacts the health and productivity of fish. However, the specific critical water analysis parameters that are most relevant to cage aquaculture in Malaysian coastal regions have not been comprehensively identified and defined, leading to uncertainties in monitoring and managing water quality. In the past, water quality detection needed manual sampling and laboratory analysis, which were time-consuming and resource intensive. This traditional approach cannot deliver real-time data. This literature examines the important water analysis parameters and contemporary technology that has the potential to be adopted by fish farmers in Malaysia and addresses the financial implications of such an adoption. The review protocol started by selecting the relevant literature and several important things were considered during the selection process. The identification and definition of critical water analysis parameters emerge as fundamental to effective water quality monitoring and management in cage aquaculture. By delineating these parameters, we can tailor monitoring strategies using recent technologies to the unique environmental conditions of Malaysian coastal regions, thus enabling more precise interventions when deviations occur.